2012
DOI: 10.1121/1.3665996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of noise suppression on intelligibility: Dependency on signal-to-noise ratios

Abstract: The effects on speech intelligibility of three different noise reduction algorithms (spectral subtraction, minimal mean squared error spectral estimation, and subspace analysis) were evaluated in two types of noise (car and babble) over a 12 dB range of signal-to-noise ratios (SNRs). Results from these listening experiments showed that most algorithms deteriorated intelligibility scores. Modeling of the results with a logit-shaped psychometric function showed that the degradation in intelligibility scores was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 31 publications
(48 reference statements)
1
32
0
2
Order By: Relevance
“…The WSTOI algorithm was evaluated using the results of the intelligibility tests in [11]. Recordings of the IEEE sentences [19] spoken by a single male speaker combined with babble or car noise were played at one of five Signal-to-Noise Ratios (SNRs) to 60 listeners in either an unprocessed condition or after having been processed using one of three noise suppressors.…”
Section: Methodsmentioning
confidence: 99%
“…The WSTOI algorithm was evaluated using the results of the intelligibility tests in [11]. Recordings of the IEEE sentences [19] spoken by a single male speaker combined with babble or car noise were played at one of five Signal-to-Noise Ratios (SNRs) to 60 listeners in either an unprocessed condition or after having been processed using one of three noise suppressors.…”
Section: Methodsmentioning
confidence: 99%
“…At Signal-to-Noise Ratios (SNRs) below about 0 dB the intelligibility of noisy speech is significantly reduced and conventional speech enhancement techniques are normally unable to improve intelligibility even though they may give substantial improvements in SNR [1,2]. A number of studies [3,4] have shown that the intelligibility of noisy speech can be improved by applying a binary-valued gain mask in the TimeFrequency (TF) domain.…”
Section: Introductionmentioning
confidence: 99%
“…For an illustration of the performance of current intrusive speech intelligibility techniques we test the STOI method on a database where subjective intelligibility scores are available [62]. The STOI [38], [40] method achieved a Spearman correlation coefficient of 0.94 with subjective word intelligibility scores validating its use for the ADN-TN and additive noise partition of the C-Qual database.…”
Section: B Labelingmentioning
confidence: 99%